Web-based geospatial multiple criteria decision analysis using open software and standards. Issue 8 (2nd August 2016) - Hamilton, Michelle C.; Nedza, John A.; Doody, Patrick; Bates, Matthew E.; Bauer, Nicole L.; Voyadgis, Demetra E.; Fox-Lent, Cate
ABSTRACT: The emerging ubiquity of geospatial information is providing an unprecedented opportunity to apply Geographical Information Systems (GIS)-based multiple criteria decision analysis (MCDA) to a broad spectrum of use cases. Volunteered geographic information, open GIS software, geoservice-based tools, cloud-based virtualized platforms, and worldwide collaboration of both domain experts and general users have greatly increased the quantity and accessibility of geospatially referenced data resources. Currently, there is a lack of GIS-based MCDA tools that integrate this decision-driven process within a widely accessible, robust geoframework environment, designed for user-friendly interaction. In this contribution, we present a conceptual workflow and proof-of-concept software application, Geocentric Environment for Analysis and Reasoning (GEAR), which provides a viable transition path to enhance geospatial MCDA in the age of open GIS. We propose a Web-based platform that leverages open-source geotechnologies to incorporate a wide variety of geospatial data formats in a common solution space to allow for spatially enhanced and time-relevant decision analysis. Through the proposed workflow, a user can ingest and modify heterogeneous data formats, exploit temporally tagged data sources, create multicriteria decision analysis models, and visualize the results in an iterative and collaborative workspace. A sample case study applied to disaster relief is used to demonstrate the prototype and workflow. This proof-of-concept Web-based application provides a notional pathway of how to connect open-source data to open-source analysis through a geospatially enabled MCDA workflow that could be virtually accessible to many levels of decision makers from individuals to entire organizations.